Pengembangan Tanaman Hidroponik dan Kreativitas Anak di Taman RPTRA Petukangan Berseri - Aris Wahyu Kuncoro; Dwi Kristanto; Hasan Ipmawan; Pambuko Naryoto; Koen Hendrawan; Marini (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
The development of hydroponic plants is one of the modern agricultural methods that is being promoted in Indonesia to increase agricultural production and reduce food imports. In Taman RPTRA Petukangan Berseri, hydroponic development is not only used as an agricultural activity, but also as a means to hone children's creativity. In this activity, children are invited to design and build a hydroponic system, choose the type of plant to be planted, and care for and harvest the harvest. This activity is expected to provide an understanding of the importance of agriculture, develop children's creativity, and provide valuable experience about responsibility in caring for the environment. The development of hydroponics and children's creative activities in Taman RPTRA Petukangan Berseri can also be an example for other regions to utilize hydroponic technology in increasing agricultural production and developing children's creativity. Through this activity, it is hoped that a young generation can be created who care about the environment and have the skills to develop agriculture sustainably.